Heterotopic Ossification with Bone Marrow Elements in an Incisional Hernial Sac: A Rare Entity - Salapathi Shanmugam; B Rajeshwari; K Ramkumar; Mitra Ghosh (Journal of Clinical and Diagnostic Research, 2023)
Heterotopic Ossification (HO) is usually seen in laparotomy wounds following gastrointestinal surgeries. The presence of marrow elements in an area of HO is very rare. A 57-year-old male with a history of omento-myelo-synangiosis for syringomyelia was admitted with an incisional hernia. A calcified nodule was detected in the wall of the hernia sac on Computed Tomography (CT). Histopathology of the excised nodule showed HO with marrow elements exhibiting trilineage haematopoiesis. HO is commonly an incidental finding during abdominal imaging for another condition. The presence of trilineage haematopoiesis within HO is extremely rare. As most of these patients are asymptomatic, conservative management is sufficient. Surgical excision is indicated, if any associated complications arise.